Plastics, rubber, and paper recycling : a pragmatic approach - Rader, Charles P., 1935-; American Chemical Society. Division of Polymer Chemistry; American Chemical Society Meeting (208th : 1994 : Washington, DC) (Washington, DC : American Chemical Society, 1995)
54